Global Ionospheric Scintillation Estimation Based on Phase Screen Modeling From One‐Dimensional Satellite Data - Yuhao Zheng; Chao Xiong; Luca Spogli; Rayan Iman; Lucilla Alfonsi (Space Weather)
Abstract Ionospheric scintillations, which usually manifest as sudden, rapid fluctuations in radio wave signal phase and amplitude, challenge the reliability of satellite communication and navigation. Based on the single phase screen assumption, this study uses the one‐dimensional (1D) in‐situ plasma density data of ESA's Swarm constellation data to develop a three‐dimensional (3D) power spectrum of electron density perturbation and construct a model to estimate scintillations caused by small‐scale ionospheric plasma density irregularities. By deriving the turbulence strength (Cs) and calculating the amplitude scintillation index S4, the global distribution of ionospheric scintillation is derived. Scintillation from our model shows typical seasonal variations, with peaks during equinoxes at both high and low magnetic latitudes. For local time (LT) dependence, the scintillation at low magnetic latitudes peaks around 21:00 LT, while at high magnetic latitudes, the maximum occurrence appears around noon, with an asymmetry between the northern and southern hemispheres. In addition, positive correlations between scintillation occurrence and solar activity, as well as geomagnetic storms are observed, with higher magnetic latitudes more being affected by geomagnetic disturbances. These features of our model‐estimated scintillations agree well with the occurrence of small‐scale plasma density irregularities at different magnetic latitudes as reported by previous studies. Our study introduces a way to estimate the global coverage of ionospheric scintillation from in‐situ satellite measurements, which cannot be achieved by the ground‐based GNSS networks due to the lack of coverage in the ocean regions.